Hubungan Pola Tidur Terhadap Tingkat Konsentrasi Belajar Siswa Kelas 12 Di SMAN 6 Kota Tangerang Selatan - Sinabutar, Nerli Adria; Kartikasari, Rizky Fitria; Ahmad , Abiyyu Faqih Dhiyaus Suud Ahmad (STIKes IMC Bintaro, 2023)
ABSTRACT Introduction : Sleep is one of the basic needs for living things to live their lives. The main factors that need to be considered in sleep are sleep quality and sleep quantity. If there is a disturbance in these factors, it will have a bad impact on the memory system and concentration. The purpose of research : to determine the relationship between sleep patterns and the level of learning concentration of class XII students at SMAN 6 Serang City.Research methods : Quantitative research design with Cross Sectional approach. The sample technique used by researchers was Stratified Random Sampling technique with a total of 96 respondents. The research instrument was a questionnaire sheet. Analysis of research data using the Chi Squere test. Results of research : Research Results: based on the results of the study, most were known to have good sleep patterns, namely 77 people (80.2%), most had high learning concentration, namely 69 people (71.9%). Conclusion : There is a relationship between sleep patterns and the level of learning concentration of class XII students at SMAN 6 Serang City (p-value 0.013; OR 3.5). Suggestion : It is expected for respondents to maintain daily sleep patterns as a way to improve concentration while studying so that learning achievement can be improved.